Manajemen Risiko dalam Pengelolaan Sumber Air Baku (Studi Kasus Sungai Cisadane Kota Tangerang) - Idi Namara; Djoko M Hartono; Yusuf Latief; Setyo Sarwanto Moersidik (Universitas Batanghari Jambi, 2022)
Cisadane River, Tangerang City, is one of the important rivers in Indonesia. This river is a source of raw water for PDAM Tangerang City and Soekarno-Hatta International Airport, but unfortunately the quality of this river water tends to decrease due to pollution. Many things have been done by the government in managing the river water, but have not brought positive changes to the raw water source. The problems that occur include urban development and changes in land use which have an influence on the burden of river pollution. The approach taken in this research is qualitative analysis and risk management. The final result of this research is the development of policies in the management of rivers as raw water sources, namely land use management, separation of drainage channels from domestic sewage, increasing the coverage of WWTP services, and strengthening institutional and regulatory aspects, especially in funding commitments.